Analisis Pengaruh Jurusan Kuliah terhadap Minat Mahasiswa untuk Berbisnis - Sodiko Hidayad (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2017)
College student is the source of inovation that can further the country. Indonesia needs their inovation, either on social and humanities scope or science and technology scope. But they choose different ways after college. There is students that want to work, and some of them want to be entrepreneur. And the purpose of this research is knowing the effect of their major to their interest of being an entrepreneur. The sample of this research is the college students from vary major in many universities. The independent variable is the major and the major category (social and humanities/science and technology) and dependent variable is the career plan and the tendency between working and doing business. The data analysis that was used is by counting the average tendency of doing business from each majors and major categories. The result of this research show that majors effect student’s interest for doing business although not significant. The students from all of major categories show that they have interest for doing business. But the tendency for doing business of social and humanities students is higher than science and technology students. The significant difference appears on the major that is strongly-related with finance/money. They have significant difference in tendency for doing business.